Strength, sorptivity and shrinkage characteristics of cow dung stabilized mud mortar. (2020) - Lekshmi, M.S.; Vishnudas, Subha; Nair, Deepa G.
Abstract: Mud is a versatile and sustainable material for construction used in the form of blocks, mortar and plaster from time immemorial. People are averse to adopt earthen constructions due to the durability concerns associated with these constructions. In order to retrieve the practice of mud construction techniques, an experimental investigation is found necessary which checks the feasibility of enhancing the durability of locally available mud using traditional admixture. The study focused on the effect of cow dung as traditional admixture on the mechanical and durability properties of mud mortar made with locally available soils in Kerala, India. Experimental results in mechanical properties of mud mortar using locally available soils with cow dung as admixture was found comparable to that of virgin mud mortar. In addition to that, to improve the durability properties of cow dung stabilized mud mortar a natural dispersing agent, cashew nut shell liquid (CNSL) was also added which imparted positive results.